Fighting Poverty through Decentralized Renewable Energy : Energy SME Conference, Phnom Penh, Cambodia - World Bank (Washington, DC, 2014)
Decentralized energy services remain at the forefront in the fight against poverty. Small and Medium Enterprises (SME) are driving this effort to provide an alternative to state-owned utilities and other large energy providers in poor and developing countries. SMEs allow entrepreneurs to provide alternative energy supply in remote and rural areas while also providing jobs, lowering energy costs, and reducing carbon and other greenhouse gas emissions. The document provided a forum to discuss the specific role of SMEs in the energy sectors of Cambodia and Lao people's democratic Republic and establish a blueprint for SME involvement in alternative energy products and services in other countries.